Hyperbaric Oxygen Therapy Alleviates Memory and Motor Impairments Following Traumatic Brain Injury via the Modulation of Mitochondrial-Dysfunction-Induced Neuronal Apoptosis in Rats - Reem Sakas; Katya Dan; Doron Edelman; Saher Abu-Ata; Aviv Ben-Menashe; Yaseen Awad-Igbaria; Jean Francois-Soustiel; Eilam Palzur (Antioxidants, 2023)
Traumatic brain injury (TBI) is a leading cause of morbidity and mortality in young adults, characterized by primary and secondary injury. Primary injury is the immediate mechanical damage, while secondary injury results from delayed neuronal death, often linked to mitochondrial damage accumulation. Hyperbaric oxygen therapy (HBOT) has been proposed as a potential treatment for modulating secondary post-traumatic neuronal death. However, the specific molecular mechanism by which HBOT modulates secondary brain damage through mitochondrial protection remains unclear. Spatial learning, reference memory, and motor performance were measured in rats before and after Controlled Cortical Impact (CCI) injury. The HBOT (2.5 ATA) was performed 4 h following the CCI and twice daily (12 h intervals) for four consecutive days. Mitochondrial functions were assessed via high-resolution respirometry on day 5 following CCI. Moreover, IHC was performed at the end of the experiment to evaluate cortical apoptosis, neuronal survival, and glial activation. The current result indicates that HBOT exhibits a multi-level neuroprotective effect. Thus, we found that HBOT prevents cortical neuronal loss, reduces the apoptosis marker (cleaved-Caspase3), and modulates glial cell proliferation. Furthermore, HBO treatment prevents the reduction in mitochondrial respiration, including non-phosphorylation state, oxidative phosphorylation, and electron transfer capacity. Additionally, a superior motor and spatial learning performance level was observed in the CCI group treated with HBO compared to the CCI group. In conclusion, our findings demonstrate that HBOT during the critical period following the TBI improves cognitive and motor damage via regulating glial proliferation apoptosis and protecting mitochondrial function, consequently preventing cortex neuronal loss.